2013
DOI: 10.1038/npp.2013.99
|View full text |Cite|
|
Sign up to set email alerts
|

An Intronic Variant in OPRD1 Predicts Treatment Outcome for Opioid Dependence in African-Americans

Abstract: Although buprenorphine and methadone are both effective treatments for opioid dependence, their efficacy can vary significantly among patients. Genetic differences may explain some of the variability in treatment outcome. Understanding the interactions between genetic background and pharmacotherapy may result in more informed treatment decisions. This study is a pharmacogenetic analysis of the effects of genetic variants in OPRD1, the gene encoding the δ-opioid receptor, on the prevalence of opioid-positive ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
2
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 52 publications
0
63
2
11
Order By: Relevance
“…Response rates vary dramatically and the use of none of these is without risks [126]. One recent study of African-Americans found that for a variant, rs678849, in the gene encoding the delta opioid receptor ( OPRD1 ), CC individuals had more positive urine tests (24 weeks post-treatment) if treated with buprenorphine but less positive tests when treated with methadone [127]. Another recent study implicates a functional variant (rs2760118) in the gene encoding the succinic semialdehyde dehydrogenase enzyme ( ALDH5A1 ) in response to methadone maintenance with T allele carriers more likely to be non-responders [128].…”
Section: Putting Your Genes To Work: Pharmacogeneticsmentioning
confidence: 99%
“…Response rates vary dramatically and the use of none of these is without risks [126]. One recent study of African-Americans found that for a variant, rs678849, in the gene encoding the delta opioid receptor ( OPRD1 ), CC individuals had more positive urine tests (24 weeks post-treatment) if treated with buprenorphine but less positive tests when treated with methadone [127]. Another recent study implicates a functional variant (rs2760118) in the gene encoding the succinic semialdehyde dehydrogenase enzyme ( ALDH5A1 ) in response to methadone maintenance with T allele carriers more likely to be non-responders [128].…”
Section: Putting Your Genes To Work: Pharmacogeneticsmentioning
confidence: 99%
“…Due to resource limitations, decisions on whether to analyze the blood genetic elements will be reviewed and analyzed case by case. Recently, some CTN trials have produced interesting genetic findings [10]. …”
Section: Discussionmentioning
confidence: 99%
“…In cardiovascular medicine, diverse approaches have identified clinically relevant (though not currently applicable) pharmacokinetic gene-medication pairs, including CYP2C19 /clopidogrel and CYP2C9 /warfarin, and pharmacodynamic pairs, including VKORC1 /warfarin and ADRB1 /bucindolol (20, 36). In addiction medicine, gene-medication pairs identified using a candidate gene approach include a non-synonymous substitution (rs1799971) in OPRM1 (which encodes the mu-opioid receptor) and naltrexone for treating alcohol dependence (37), a variant (rs2832407) in GRIK1 (which encodes the GluK1 subunit of the kainate receptor) and topiramate treatment of heavy drinking (38), two variants (5′-HTTLPR and rs1042173) in SLC6A4 (which encodes the serotonin transporter) and ondansetron (39), and a variant (rs678849) in OPRD1 (which encodes the delta-opioid receptor) and buprenorphine or methadone treatment of opioid dependence (40). However, these gene-medication pairs have either failed to replicate in a prospective study design ( OPRM1 /naltrexone (41) or have not yet been evaluated prospectively ( GRIK1 -topiramate, SLC6A4 /ondansetron, OPRD1 /opioid agonists).…”
Section: Identifying Biomarkers Of Treatment Responsementioning
confidence: 99%